2013
DOI: 10.1108/ijbm-02-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach for understanding Islamic home financing adoption in Malaysia

Abstract: Purpose -The purpose of this paper is to investigate the effects of subjective norm, relative advantage, simplicity, compatibility and perceived behavioural control on the Islamic home financing adoption. It also examines the effects of subjective norm, relative advantage, simplicity and compatibility on attitude. Analyses of attitude as a mediating factor are also provided. Design/methodology/approach -Survey data from 237 usable questionnaires are employed to test the hypothesized relationships. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
121
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 47 publications
13
121
1
1
Order By: Relevance
“…Previous studies have established that attitude can predict the behavioral intention to patronize Islamic financial services instrument (Abdul Amin, 2012;Amin, Abdul Rahman, and Abdul Razak, 2013;Amin et al, 2014a, b;Amin, Rahman, and Ramayah, 2013;Sharma et al, 2016). Although there are numerous studies on the behavioral intention to choose IHF instrument such as MM (Amin, Abdul Rahman, and Abdul Razak, 2013;Amin et al, 2014a, b;Md Taib et al, 2008;Usman and Lizam, 2016), it is interesting to note that most of them were carried out on ICB context, and none was done within the context of financial cooperatives. As argued by scholars such as Ebrahim (2009) and Mydin Meera and Abdul Razak (2005), the current MM practices in ICB reveal a marked departure from its Note: Path between intention and behavior will not be estimated…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies have established that attitude can predict the behavioral intention to patronize Islamic financial services instrument (Abdul Amin, 2012;Amin, Abdul Rahman, and Abdul Razak, 2013;Amin et al, 2014a, b;Amin, Rahman, and Ramayah, 2013;Sharma et al, 2016). Although there are numerous studies on the behavioral intention to choose IHF instrument such as MM (Amin, Abdul Rahman, and Abdul Razak, 2013;Amin et al, 2014a, b;Md Taib et al, 2008;Usman and Lizam, 2016), it is interesting to note that most of them were carried out on ICB context, and none was done within the context of financial cooperatives. As argued by scholars such as Ebrahim (2009) and Mydin Meera and Abdul Razak (2005), the current MM practices in ICB reveal a marked departure from its Note: Path between intention and behavior will not be estimated…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…TRA is open to modification or extension by altering the path and including additional predictors if it can be shown to capture a greater proportion of variance in intention after the original constructs have been taken into account [31]. This theory is appropriate for this study as it has been shown to be applicable in various other contexts of Islamic marketing such as in the halal food purchasing [35,36], Islamic insurance [37], Islamic pawn shops [38], Islamic home financing [39], Islamic personal financing [37], Islamic credit cards [40] and Islamic mobile phone banking [41].…”
Section: Theory Of Reasoned Action (Tra)mentioning
confidence: 99%
“…A previous study that investigated cosmetics consumption among young adult Muslim consumers found that awareness of halal cosmetics is still low among young adult consumers [3]. As the study was conducted among young Muslims in Malaysia using qualitative analysis, it was suggested that scholars seek to examine young Muslims' cosmetics consumer behavior in different Islamic contexts, such as Brunei or Indonesia [5]. The current study strives to investigate young Muslim consumers' attitudes and intention regarding the consumption of halal cosmetics in the Indonesian context using a quantitative approach.…”
Section: Introductionmentioning
confidence: 99%